Integrating Ukraine into European grid infrastructure - Zagorodny, A.; Zgurovsky, M.; Zinovjev, G.; Martynov, E.; Petrenko, A. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2009)
Ukrainian Grid community has established Ukrainian National Grid Initiative (UNGI) which has joined up the major active European projects EGEE and EGI. The community of objectives based on the involvement in world leading scientific projects is elucidated. General features of UNGI and European Grid structures and projects together with various Grid-based applications supported by UNGI are discussed. Current UNGI activities and its future plans in view of realistic computational and human resources are described. The problems and prospects of rapidly progressing Ukrainian Grid infrastructure on the way of international cooperation and integration are illuminated. Украинские специалисты в области грид-технологий начали реализацию Украинской национальной грид-инициативы (УНГИ), которая входит в главные действующие европейские проекты EGEE и EGI. Обоснована перспективность и необходимость участия в ведущих мировых научных проектах. Рассматриваются общие черты и характеристики УНГИ, а также европейских грид-структур и проекттов, акцентируется внимание на возможности решения прикладных грид-задач в рамках УНГИ. Представляются современное состояние УНГИ, ее вычислительный и кадровый потенциал. Описываются проблемы и перспективы развития УНГИ, а также пути и способы международной кооперации. Українські фахівці з грід-технологій розпочали реалізацію Української національної грід-ініціативи (УНГІ), що входить до головних діючих європейських проектів EGEE та EGI. Обґрунтовано перспективність і необхідність участі в провідних світових наукових проектах. Розглядаються загальні риси і властивості УНГІ та європейських грід-структур і проектів, акцентується увага на можливості вирішувати
прикладні грід-задачі у рамках УНГІ. Представлено сучасний стан УНГІ, її обчислювальний і кадровий потенціал. Описуються проблеми і перспективи розвитку УНГІ, а також шляхи і способи міжнародної кооперації.